Curiosity, intellectual ambition and knowledge: "que sais-je?" - Unger, Roberto (2022)
Curiosity receives different considerations over time: bad habit, lust, vice, and virtue. The analyzes of different times and authors permeate religion, prejudices and, finally, science, which enshrines it. Is the most active faculty in childhood and adolescence and enables the development of the general aptitudes of the mind. In the remote past it was condemned by religion and considered responsible for the fall of the Adamic civilization as well as the misfortune of the mythical Pandora. Currently, researches point out that curiosity increases with uncertainty and awakens the search for knowledge. Understanding the neural basis of curiosity has important substantive implications allowed us to observe that search for information is evolutionarily adaptive. Modern technologies and internet expand the amount of information available, therefore increasing the potential effects of curiosity. The archetype intellectual ambition and the concept of knowledge are used to understand the enhancement of the intellect along with curiosity.